THE EFFECT OF APPLICATION OF RETURN ON ASSETS, LEVERAGE, COMPANY SIZE AND INSTITUTIONAL OWNERSHIP ON TAX AVOIDANCE IN REGISTERED MANUFACTURING COMPANIES IN THE TRANSPORTATION AND LOGISTICS SECTOR ON THE INDONESIAN STOCK EXCHANGE 2019-2022 - Raymon Ardian Zebua; Sahwita Angkat; Wilsa Road Betterment Sitepu; Owen de Pinto Simanjuntak (Journal Accounting International Mount Hope, 2024)
The aim of this research is to prove whether there is an influence of Return on Assets, Leverage, Company Size and Institutional Ownership on Tax Avoidance in Transportation and Logistics Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI). This research uses quantitative research using the SPSS version 26 application. The population used in this research is transportation and logistics sector manufacturing companies registered on the BEI for the 2019-2022 period. The results of this research show that (1) Return On Assets has a significant effect on Tax Avoidance, (2) Leverage does not have a significant effect on Tax Avoidance. (3) Company size has a significant effect on Tax Avoidance. (4) Institutional ownership has a significant effect on Tax Avoidance. The results of the Classical Assumption Test which went through the Normality test process, Multicollinearity Test, Autocorrelation Test, Heteroscedasticity Test, Multiple Linear Regression Test, Hypothesis (T Test), Hypothesis (F Test), Coefficient (R2) and Adjusted R Square had a 34% effect on Tax Avoidance and the remaining 66% are influenced by other variables.